Tri-Electrode fushoku test kit - Muhammad Sahrulfahmi, Md Senan; Mohamad Athmar Afiq, Shalahuddin; Muhammad Syazrin, Rasdi; Nur Halimahtun, Manap; Nurainaa, Mohd Yusof; Juliawati, Alias (2021)
General test rig is not feasible since the test must be setup manually and it required more time. Commercial potentiodynamic test rig is not flexible since it can test certain shape of material or sample only. Commercial potentiodynamic polarization technique has a safety issue risk since the beaker for the experiment not very stable and easy to fall. The price for a current test rig is expensive.